1999
DOI: 10.1007/s004310051155
|View full text |Cite
|
Sign up to set email alerts
|

Oral vitamin K 1 prophylaxis for newborns with a new mixed-micellar preparation of phylloquinone: 3 years experience in Switzerland

Abstract: With the introduction of two oral doses of a mixed-micellar vitamin K1 preparation administered in the 1st week of life, the incidence of late vitamin K1-deficiency-bleeding has decreased from 7.2:100,000 between 1986-1987 to 2.8:100,000 between 1995 and 1998. This regimen may be suitable for prophylaxis of vitamin K1-deficiency-bleeding, however, it does not fully protect infants with cholestatic disease from late-onset bleeding. If oral prophylaxis is considered for these infants, vitamin K1 has to be admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
1
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 16 publications
1
15
1
2
Order By: Relevance
“…Although vitamin K 1 is well established as a cofactor for the complete hepatic synthesis of some plasma coagulation factors [13], our data show that it also triggers vascular actions when oxygen levels are low. Vitamin K 1 has clinical applications, as it has been used in the prophylaxis of vitamin K 1 deficiency bleeding in infants [14]. In spite of this clinical use of vitamin K 1 , we must be fully aware of its potential vascular effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although vitamin K 1 is well established as a cofactor for the complete hepatic synthesis of some plasma coagulation factors [13], our data show that it also triggers vascular actions when oxygen levels are low. Vitamin K 1 has clinical applications, as it has been used in the prophylaxis of vitamin K 1 deficiency bleeding in infants [14]. In spite of this clinical use of vitamin K 1 , we must be fully aware of its potential vascular effects.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin K 1 (Konakion ® , Hoffmann-La Roche, Basel, Switzerland) is widely used for the prophylaxis of vitamin K 1 deficiency bleeding in infants [14]. However, little is known about the vascular actions of this vitamin; though it has been reported that vitamin K 1 is able to inhibit the synthesis of prostacyclin (PGI 2 ), a vasodilatory arachidonic acid metabolite, in cultured bovine aortic endothelial cells [15].…”
Section: Introductionmentioning
confidence: 99%
“…Although this might be true in healthy infants [36], epidemiological data do not show an improved efficacy of the MM preparation [47]. Absorption after oral administration remains poor in cholestatic patients, those most at risk for late vitamin K deficiency bleeding (VKDB) [32,37,47].…”
Section: Key Messagementioning
confidence: 98%
“…Lebensmonat auftreten können, ist wohl zurückgegangen, aber nicht ganz verschwunden. Betrafen Spätblutungen in den Jahren 1986 -1988 noch 7,1/100 000 Neugeborene, so waren es in den letzten 6 Jahren noch 2,6/100 000 [1,4,5]. 14 von 19 in den letzten 6 Jahren von Spätblutungen betroffene Kinder hatten ein angeborenes Leberleiden, das erst nach Auftreten der Blutung diagnostiziert wurde.…”
unclassified
“…Les hémorragies dites tardives, pouvant survenir après quelques semaines de vie et jusqu'à l'âge de 6 mois, ont vu leur incidence diminuer mais n'ont pas disparu. S'il y en avait 7,1/100 000 nouveau-nés en 1986 -1988, il y en a eu encore 2,6/100 000 ces six dernières années [1,4,5]. Des 19 nourrissons ayant présenté une hémorragie tardive ces six dernières années, 14 souffraient d'une hépato-pathie non diagnostiquée auparavant.…”
unclassified